The emerging role of cardiovascular risk factor-induced mitochondrial dysfunction in atherogenesis - Puddu, Paolo (BioMed Central, 2009)
An important role in atherogenesis is played by oxidative stress, which may be induced by common risk factors. Mitochondria are both sources and targets of reactive oxygen species, and there is growing evidence that mitochondrial dysfunction may be a relevant intermediate mechanism by which cardiovascular risk factors lead to the formation of vascular lesions. Mitochondrial DNA is probably the most sensitive cellular target of reactive oxygen species. Damage to mitochondrial DNA correlates with the extent of atherosclerosis. Several cardiovascular risk factors are demonstrated causes of mitochondrial damage. Oxidized low density lipoprotein and hyperglycemia may induce the production of reactive oxygen species in mitochondria of macrophages and endothelial cells. Conversely, reactive oxygen species may favor the development of type 2 diabetes mellitus, mainly through the induction of insulin resistance. Similarly - in addition to being a cause of endothelial dysfunction, reactive oxygen species and subsequent mitochondrial dysfunction - hypertension may develop in the presence of mitochondrial DNA mutations. Finally, other risk factors, such as aging, hyperhomocysteinemia and cigarette smoking, are also associated with mitochondrial damage and an increased production of free radicals. So far clinical studies have been unable to demonstrate that antioxidants have any effect on human atherogenesis. Mitochondrial targeted antioxidants might provide more significant results.